Product Purchasing Decisions as a Result of Product Innovation and Sales Promotion - Kiki Aminah; Wawan Hermawan; Deni Budiana (Almana : Jurnal Manajemen dan Bisnis, 2022)
Purchasing decisions greatly affect the success of a business, if purchasing decisions increase, the sales volume will increase, which will have a positive impact on the company to continue to maintain the business. This study aims to determine that purchasing decisions of Wardah Cosmetic Products as a result of Product Innovation and Sales Promotion. This study also to find out how big the influence of product innovation on purchasing decisions, the effect of sales promotion on purchasing decisions, the effect of product innovation and sales promotion on purchasing decisions of wardah cosmetic products. The research method used in this study is descriptive and verification methods using path analysis techniques. The research results stated that the Product Innovation was in a good category, the Sales Promotion was in a good category, and the Purchase Decision was in a good category. The results of the t-test carried out show that the Product Innovation variable affects Purchase Decisions, and the Sales Promotion variable affects Purchase Decisions. The results of the f-test that were carried out showed that Product Innovation and Sales Promotion on Purchase Decisions.